2005
DOI: 10.1152/ajpcell.00561.2004
|View full text |Cite
|
Sign up to set email alerts
|

K+ channel KVLQT1 located in the basolateral membrane of distal colonic epithelium is not essential for activating Cl secretion

Abstract: The cellular mechanism for Cl(-) and K(+) secretion in the colonic epithelium requires K(+) channels in the basolateral and apical membranes. Colonic mucosa from guinea pig and rat were fixed, sectioned, and then probed with antibodies to the K(+) channel proteins K(V)LQT1 (Kcnq1) and minK-related peptide 2 (MiRP2, Kcne3). Immunofluorescence labeling for Kcnq1 was most prominent in the lateral membrane of crypt cells in rat colon. The guinea pig distal colon had distinct lateral membrane immunoreactivity for K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…Previous studies in the adult digestive tract have provided evidence of Kcnq1 expression in the parietal cells of the stomach (Dedek and Waldegger, 2001) as well as in crypt cells of the colon and small intestine (Bleich and Warth, 2000). A putative role in potassium conductance-mediated acid and/or chloride secretion of Kcnq1 in these cells have been proposed (Liao et al, 2005). Our data support that potassium conductance in the epithelial lining of the digestive tract seems to be established at an early stage of development.…”
Section: K Channel Pore-forming Subunits In Developing Digestive Systemsupporting
confidence: 85%
“…Previous studies in the adult digestive tract have provided evidence of Kcnq1 expression in the parietal cells of the stomach (Dedek and Waldegger, 2001) as well as in crypt cells of the colon and small intestine (Bleich and Warth, 2000). A putative role in potassium conductance-mediated acid and/or chloride secretion of Kcnq1 in these cells have been proposed (Liao et al, 2005). Our data support that potassium conductance in the epithelial lining of the digestive tract seems to be established at an early stage of development.…”
Section: K Channel Pore-forming Subunits In Developing Digestive Systemsupporting
confidence: 85%
“…The functional segments demarcated by our study appear to have two easily identifiable anatomical features. First, the proximal portion of the colon that expresses abundant NHE3 but scant DRA (0 -20% length) roughly corresponds to the segment that displays serosal palmleaf striations (21,31,55). Second, the portion of the rodent distal colon that is deficient in NHE3 (60 -100% colon length in rats and 75-100% in mice) is largely comprised of the extraperitoneal segment that extends from the pelvic brim to the anus; previous studies have indicated that this segment, sometimes called the rectum (30), uniquely exhibits aldosterone-stimulated electrogenic Na ϩ absorption and a weaker Cl Ϫ secretory capacity (7,30,43).…”
Section: Discussionmentioning
confidence: 99%
“…Primers for Y2-NpR were (forward primer) 5Ј-aaa tgg gtc ctg tcc tct gcc-3Ј(353-373) and (reverse primer) 5Ј-tgc ctc cgc tgg tgg tag tgg-3Ј(774-794). Proteins were isolated from colonic mucosa as described previously (33,52). Briefly, after disruption by sonication in a buffered solution containing protease inhibitors, epithelial cell lysates were centrifuged to obtain a membrane sample.…”
Section: Methodsmentioning
confidence: 99%
“…Colonic tissues were fixed after isolation, as described previously (33,52). Briefly, isolated mucosal sheets were chemically fixed followed by dehydration, sectioning, and mounting on gelatin-coated slides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation